2023
DOI: 10.3389/fmicb.2023.1290952
|View full text |Cite
|
Sign up to set email alerts
|

Ceragenins exhibit bactericidal properties that are independent of the ionic strength in the environment mimicking cystic fibrosis sputum

Karol Skłodowski,
Łukasz Suprewicz,
Sylwia Joanna Chmielewska-Deptuła
et al.

Abstract: The purpose of the work was to investigate the impact of sodium chloride (NaCl) on the antimicrobial efficacy of ceragenins (CSAs) and antimicrobial peptides (AMPs) against bacterial and fungal pathogens associated with cystic fibrosis (CF) lung infections. CF-associated bacterial (Pseudomonas aeruginosa, Ochrobactrum spp., and Staphylococcus aureus), and fungal pathogens (Candida albicans, and Candida tropicalis) were used as target organisms for ceragenins (CSA-13 and CSA-131) and AMPs (LL-37 and omiganan). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Nevertheless, for a more reliable assessment of ceragenin antibiofilm efficacy, experiments must be performed under conditions mimicking CF lungs, such as artificial sputum media (ASM), synthetic cystic fibrosis media (SCFM), or CF sputum samples. Accordingly, we recently reported that ceragenins preserve bactericidal activity in the environment mimicking CF sputum irrespective of its ionic strength [ 66 ]. Furthermore, the effect of the microbial cell morphology [ 56 ] and Pf bacteriophages representing various phylogenetic lineages [ 21 ] on the viscoelastic properties of biofilms should be addressed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, for a more reliable assessment of ceragenin antibiofilm efficacy, experiments must be performed under conditions mimicking CF lungs, such as artificial sputum media (ASM), synthetic cystic fibrosis media (SCFM), or CF sputum samples. Accordingly, we recently reported that ceragenins preserve bactericidal activity in the environment mimicking CF sputum irrespective of its ionic strength [ 66 ]. Furthermore, the effect of the microbial cell morphology [ 56 ] and Pf bacteriophages representing various phylogenetic lineages [ 21 ] on the viscoelastic properties of biofilms should be addressed in further studies.…”
Section: Discussionmentioning
confidence: 99%